Obstacles in prostate cancer screening: Current issues and future solutions. (March 2019) - Patel, Benjamin; Sriprasad, Seshadri; Cadeddu, Jeffrey; Thind, Arron; Rane, Abhay
Prostate cancer is the most common cancer in men and is associated with unacceptably high mortality rates, yet an accurate and acceptable screening programme that detects clinically significant prostate cancer remains elusive. Although there is good evidence that prostate-specific antigen (PSA)-based screening lowers prostate cancer-specific mortality, especially when conducted at high intensity, the harm caused by overinvestigation, overdiagnosis and overtreatment of clinically insignificant cases arguably outweighs these benefits. Several attempts have therefore been made to improve screening, enhancing the diagnostic value of PSA and identifying novel modalities for screening. Here, we provide a comprehensive review of the benefits and harms, and analyse which of these novel screening methods show most promise. Level of evidence: 5, expert opinion